The IMF: Dogma versus Unorthodoxy Can we afford another Clash? - Yang Razali Kassim (2016)
ON THE 10th anniversary of the 1997 Asian Financial Crisis, a group of former policymakers directly involved in tackling the regional upheaval huddled in Singapore with analysts for some self-reflection. Debating the key lessons from the turmoil at a conference organized by the S. Rajaratnam School of International Studies (RSIS) were such personalities as Hubert Neiss, Eisuke Sakakibara, better known as “Mr Yen”, and Soedrajad Djiwandono. A number of serving officials were also there, such as those from the Monetary Authority of Singapore and the Bank of Thailand – the central bank of the country where the crisis began. There were also prominent economists like K.S Jomo, who now serves as Assistant Secretary-General of economic affairs at the United Nations, and Lim Chong Yah, the guru of many an economist and currently professor at Nanyang Technological University.